2018
DOI: 10.4103/sjg.sjg_518_17
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and clinical predictors of LPR among patients diagnosed with GERD according to the reflux symptom index questionnaire

Abstract: Background/Aims:Gastroesophageal reflux disease (GERD) is a common condition that can lead to significant morbidity. Laryngopharyngeal reflux (LPR) is a distinct clinical entity that can occur simultaneously with GERD, necessitating additional treatment measures. The degree of overlap and clinical predictors of LPR among patients with GERD remains unknown. We aim to measure the prevalence of LPR in patients with GERD and identify clinical predictors.Patients and Methods:We performed a cross-sectional study inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 17 publications
(20 reference statements)
0
7
0
2
Order By: Relevance
“…Furthermore, more Eastern Asian otolaryngologists prescribed GI endoscopy for patients complaining of heartburn or stomach acid coming up than Western Asian otolaryngologists. For three decades, the overall trend has been to consider LPR and GERD to be different diseases [ 2 , 28 ], but many studies have shown a relationship between the two diseases [ 29 , 30 ]. Thus, digestive symptoms such as heartburn and regurgitation—both considered to be major symptoms of GERD—should be carefully evaluated when diagnosing LPR [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, more Eastern Asian otolaryngologists prescribed GI endoscopy for patients complaining of heartburn or stomach acid coming up than Western Asian otolaryngologists. For three decades, the overall trend has been to consider LPR and GERD to be different diseases [ 2 , 28 ], but many studies have shown a relationship between the two diseases [ 29 , 30 ]. Thus, digestive symptoms such as heartburn and regurgitation—both considered to be major symptoms of GERD—should be carefully evaluated when diagnosing LPR [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Laryngopharyngeal reflux (LPR)—also known as extraesophageal reflux—is an inflammatory condition of the upper aerodigestive tract related to the direct and indirect effects of gastric or duodenal content reflux, which induces morphological changes in the upper aerodigestive tract [ 1 ]. Gastroesophageal reflux disease (GERD) is also caused by the reflux of gastric content, but the two conditions show many differences in symptoms, manifestations, and response to treatment [ 2 ]. The most important difference between LPR and GERD is that the majority of patients with LPR do not have esophagitis; furthermore, fewer digestive-related symptoms are generally reported in patients with GERD [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…3 Both mechanisms alter the local physiology of the larynx and its surrounding structures leading to varying degrees of dysphonia, hoarseness, nonproductive throat clearing, sensation of postnasal drip, globus pharyngeus, and cough. 1 As health and healthcare inequities persist throughout the United States, there remains a lack of literature addressing disparities in LPR. 4 Over the last decade, the diagnosis of LPR has increased by 500%, accounting for nearly 10% of Otolaryngologic visits, and affects all racial and ethnic groups in the US.…”
Section: Introductionmentioning
confidence: 99%
“… 1 Approximately half of all adults experience symptoms in their lives. 2 3 Among the various causes, acid and bile juice reflux into the esophageal mucosa are known to be the main causes. 4 5 Diverse types of management, such as lifestyle modifications, medications, endoscopic intervention and surgery are adopted for treatment of GERD.…”
Section: Introductionmentioning
confidence: 99%